Pengaruh Brisk Walking Exercise terhadap Nilai Tekanan Darah pada Lansia Penderita Hipertensi di Posyandu Nusa Indah Kabupaten Sukoharjo - Kharisma Wahyu Widodo; Eska Dwi Prajayanti (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Old age is a phase of change caused by the aging process. One of the health problems experienced by the elderly is hypertension. Hypertension in the elderly usually occurs due to degenerative factors. to determine the effect of brisk walking exercise on blood pressure in elderly people with hypertension. using experimental Quasy with one group pre-test and post-test design. A sample of 33 respondents was selected using purposive sampling techniques. Bivariate test using the Wilcoxon test. The intervention was carried out three times in one week, with a duration of 20 minutes per session. univariate test results before 154.52/93.70 mmHg and after 146.33/86.30 mmHg. The results of the bivariate test showed a significant decrease in systolic and diastolic blood pressure after the intervention (p < 0.05). This study is effective in lowering blood pressure in elderly people with hypertension. So there is an effect of the intervention  of brisk walking exercise on the blood pressure value of elderly people with hypertension at Posyandu Nusa Indah, Cemani Village.